Exploring the nexus of corporate governance and intellectual capital efficiency: from the lens of profitability - Shahzad, K. (Springer Science and Business Media B.V., 2022)
Previous literature revealed that corporate governance (CG) attributes enhance firm performance. However, scant empirical research is available on how the CG attributes improve the intellectual capital (IC) efficiency. To fill this gap, the present study explores the effect of CG on IC efficiency. This study also intends to explore the moderating role of profitability on the nexus of CG and IC to identify whether it affects physical and intellectual capabilities. Using the census sampling technique, this study utilized the panel data of services firms in Pakistan over the period 2016â2020. The study adopted Pulicâs model for computing IC efficiency, i.e., the value-added intellectual capital coefficient model. Fixed-effect model and two-stage least squares were utilized for the regression analysis. The studyâs findings revealed that independent directors, the board size, audit committee, and remuneration committee have a significant negative relationship with IC efficiency. CEO duality has demonstrated a significant positive nexus with IC efficiency. Interestingly, the negative coefficient of audit and remuneration committees becomes positive with the moderation of profitability. This study adds to the literature on the vital role of CG in fostering IC efficiency. The findings of this study might be helpful for the policymakers, practitioners, and researchers to put in place a solid corporate governance structure that enhances physical and intellectual capabilities. Â© 2022, The Author(s), under exclusive licence to Springer Nature B.V.